A Study on \(I\)-localized Sequences in \(S\)-metric Spaces - Banerjee, Amar Kumar; Hossain, Nesar (Communications in Mathematics and Applications, 2023)
In this paper, we study the notion of \(I\)-localized and \(I^*\)-localized sequences in \(S\)-metric spaces. Also, we investigate some properties related to \(I\)-localized and \(I\)-Cauchy sequences and give the idea of \(I\)-barrier of a sequence in the same space. Finally, we use this idea for an \(I\)-localized sequence to be \(I\)-Cauchy when the ideal \(I\) satisfies the condition (AP).